Assessment competences professionals - Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2014)
Corporate social – economic development based on existing knowledge of reality. Finally, in order to say what will happen tomorrow, need to know what available today that was yesterday is. This is not feasible without appropriate methods, it is impossible without knowledge to use quantitative methods for identification social and economical expressions, it is impossible without specific, professional and general competences.This paper demonstrated that the development professional and general competences of accounting professionals, of chartered accountant is importantly under such situation the constantly changing reality. It demonstrates the need for the natural development of general and professional competences. The natural demand the development general and professional competences must be in character for the accounting professionals.It is argued that the professional, business and social competences in the most practical and relevant experience of each accounting professional activities. Success in practical activities linked to cognition the existing competences. This cognition indicated the knowledge of the quantitative assessment the existing competences and development of general and professional competences. This paper proposes and discusses the methodology to give the quantitative indicators for measure the stature of competences.
Keywords: general competence; professional competence; quantitative assessment of competences